(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
In this paper, the play by A.P. Chekhov, which is written in the best tradition of W. Shakespeare. A.P. Chekhov in The Seagull, like the English playwright, introduces into the structure of comedy an insert performance, a novice writer